Micromorphlogical analysis of sex organ development and SDS-PAGE profile of male flowers at their later developmental stages in cucumber (Cucumis sativus L.) - YUAN Gao-feng; ZHAO Pu-qing; SUN Hai-yan; WANG Qiao-mei (浙江大学学报. 农业与生命科学版)
Morphological analysis was conducted on differentiation and development of female and male sex organs during floral bud initiation and sex differentiation process in Cucumis sativus L and the results showed that the development of female and male flowers can be divided into 10 stages, and the formation of cucumber unisexual flowers initially went through a hermaphoroditic stage, then developed toward maleness or femaleness. No significant morphological difference existed between female and male flowers until hermaphoroditic stage (Stage V). The developmental destination of the inappropriate organs (the stamen in female flowers and carpels in male flowers) was further studied, and the results showed that the stamens in female flower sooner or later stopped growth, but did not disappear during the formation of female flower; while the carpels in male flower grew continuously throughout the development of male flower. SDS-PAGE analysis of carpels showed that new proteins were synthesized in the carpels of male flowers at later development stages, indicating that their organs were still metabolically active.